Using English as a Means of Instruction (EMI) in Teaching Content Subjects (Universitas Islam Negeri Sunan Ampel Surabaya, 2015)
A foreign language will be more effectively learned when integrated with content rather than isolated as a learned subject; thus the language should be more used in contexts than just formally learned. Recent language teaching methods have been geared toward involving both content and language teaching simultaneously, referred as CLIL, CBI, EMI or L2 use. This article is aimed at describing the use of L2 in teaching content subjects by looking at the attitudes of the students and the interaction between students and teachers at a university in Indonesia. Using mixed research method by conducting survey and non-participant observation to obtain the data about the classroom interaction and attitudes of the students in EMI classes, this study reveals that students’ attitude towards EMI classes is at a moderate to high level. The classroom interaction has been mostly done in English. Both the students and the lecturers use English in the classroom when they are involved in activities up to a certain level for content understanding. In addition, it is common to find code mixing or code switching during interaction. This can be due to their awareness of the benefits and advantages of having more English interaction in this program.